Preparation method and application of mesoporous confinement nickel-based methane dry reforming catalyst
By confining nickel and cobalt domains in the pores of SBA-15 mesoporous molecular sieve, a mesoporous domain-limited nickel-methane dry reforming catalyst was prepared, which solved the problem of catalyst inactivation at high temperatures and achieved efficient photothermal synergistic catalytic performance.
Patent Information
- Application Number
- CN202411805987.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
AI Technical Summary
Existing nickel-based methane dry reforming catalysts are prone to carbon deposits and metal nickel sintering at high temperatures, resulting in catalyst deactivation, and precious metal catalysts are expensive, limiting industrial applications.
The preparation method of nickel-based methane dry reforming catalyst with mesoporous domains is adopted. By confining nickel and cobalt domains in the pores of SBA-15 mesoporous molecular sieve, it is uniformly distributed in the pores to form nickel-cobalt bimetallic nanoparticles, and ethylene glycol is used as a surfactant to enhance the dispersion and stability of the metal particles.
The uniform dispersion and stability of the catalyst metal particles is achieved, the carbon deposit and sintering phenomenon is suppressed, the catalyst's resistance to carbon deposit and sintering ability is improved, and its performance in photothermal synergistic catalysis is enhanced.
Smart Images

Figure CN119680616A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano catalyst preparation, and specifically relates to a preparation method and application of a mesoporous confined nickel-based methane dry reforming catalyst. Background Art
[0002] At present, the utilization of natural gas is mainly divided into two ways: direct method and indirect method. The direct method is to produce organic substances such as methanol by high-temperature cracking or partial oxidation of natural gas. However, this method has certain complexities in tail gas treatment and pure oxygen use, which limits its industrial application. The indirect method is to convert natural gas into synthesis gas (H2 and CO) first, and then use the synthesis gas as a raw material to further convert it into methanol, ethanol or other liquid fuels through processes such as Fischer-Tropsch synthesis. Since the indirect method is easy to implement, it has received widespread attention. The methane dry reforming technology using methane and carbon dioxide as reactants can produce a synthesis gas H2 / CO close to 1, which is suitable for further Fischer-Tropsch synthesis. In addition, methane dry reforming also consumes CO2, which is beneficial to reducing the concentration of greenhouse gases in the atmosphere, so it has attracted much attention. However, methane dry reforming requires very high temperatures to be activated (above 750°C). High temperatures not only lead to excessive energy consumption, but also cause catalyst sintering and carbon deposition, which deactivates the catalyst, thereby limiting its industrial application value. How to activate the methane dry reforming reaction at a lower temperature and inhibit carbon deposition and sintering is the top priority in the current research on methane dry reforming catalysts.
[0003] In recent years, the advantages of photocatalytic technology have been reported by many scholars. Compared with thermal catalytic methane dry reforming, photocatalytic technology can reduce the reaction temperature of methane dry reforming, avoid catalyst sintering, and thus improve the stability of the catalyst. At present, the research on photocatalysts is mainly focused on precious metals such as Au, Pt, Rh, Ru, and Ir, because they have good LSPR (localized surface plasmon resonance) effect and can obtain excellent methane dry reforming catalytic performance under light, but their high price limits their industrial application. Nickel-based catalysts have attracted much attention because of their low price and high methane dry reforming activity. However, nickel-based catalysts have a fatal disadvantage. Under long-term high-temperature reaction, nickel-based catalysts are prone to carbon deposition and metal nickel sintering, which causes catalyst deactivation. Studies have shown that small-sized nickel nanoparticles can inhibit the growth of carbon fibers, thereby achieving the purpose of anti-carbon deposition. In addition, most of the light of nickel-based catalysts will be converted into heat to participate in the methane dry reforming reaction during photocatalysis, resulting in low light utilization efficiency.
[0004] The current design strategy of nickel-based methane dry reforming catalyst is to load nickel onto a carrier to make it better dispersed and prevent nickel agglomeration through strong metal-carrier interaction. Methane dry reforming needs to be carried out at high temperatures, so the selected carrier must have good thermal stability, such as SiO2, Al2O3, MgO, La2O3-ZrO2, etc. It is reported that the nickel-based catalyst loaded with SBA-15 mesoporous molecular sieve has the advantage of high dispersion, but it is difficult for all metal particles to enter the molecular sieve pores, and some metals are still attached to the outer surface of the mesoporous pores, so there are still problems such as sintering and carbon deposition. Summary of the invention
[0005] In view of the fact that in the preparation process of the existing nickel-based methane dry reforming catalyst, it is difficult for all metal particles to enter the molecular sieve pores, and a part of the metal is still attached to the outer surface of the mesoporous pores, causing the catalyst to still have the problems of sintering and carbon deposition. The present invention provides a preparation method and application of a mesoporous confined nickel-based methane dry reforming catalyst.
[0006] Technical solution: A method for preparing a mesoporous confined nickel-based methane dry reforming catalyst, wherein the catalyst uses a mesoporous molecular sieve as a carrier, and nickel and cobalt are confined in the pores of the mesoporous molecular sieve; the nickel and cobalt are uniformly distributed in the pores.
[0007] Preferably, the pore size of the mesoporous molecular sieve is 6nm to 11nm, the material of the mesoporous molecular sieve is silicon dioxide, and the mesoporous molecular sieve is SBA-15; the loading amount of nickel and cobalt is 5.5wt% to 12wt% of the total mass of the catalyst, wherein the nickel loading amount is 5wt% to 10wt%, and the cobalt loading amount is 0.5wt% to 3wt%.
[0008] Preferably, the preparation method comprises the following steps:
[0009] Step 1: Mix a nickel precursor salt, a cobalt precursor salt, an SBA-15 carrier and an appropriate amount of ethylene glycol in a certain amount of water to obtain a mixed solution, stir and evaporate the mixed solution under the condition of heating in an oil bath at 40° C. to 80° C., and then dry at 90° C. to 120° C. for at least 12 hours;
[0010] Step 2: Grind the dried sample for 10-15 minutes and then put it into a tube furnace. Calcinate it in an air atmosphere for 2-6 hours and then cool it to room temperature. The calcination conditions are: 400-600°C, a heating rate of 2°C / min, and an air flow rate of 50-100 mL / min.
[0011] Step 3: Use hydrogen programmed temperature reduction, first pass Ar to remove the air in the tubular furnace and then switch to H2, with an H2 flow rate of 10-40 mL / min, a heating rate of 10°C / min, and reduction at 500°C-700°C for 2h-6h. The formed nickel-cobalt bimetallic nanoparticles are evenly anchored in the mesoporous carrier, and a nickel-cobalt bimetallic methane dry reforming catalyst grown in ordered mesopores is obtained.
[0012] Preferably, in step 1, the nickel precursor salt is nickel nitrate hexahydrate, nickel acetate tetrahydrate or nickel oxalate dihydrate, and the cobalt precursor salt is cobalt nitrate hexahydrate, cobalt acetate tetrahydrate or cobalt oxalate dihydrate.
[0013] Preferably, in step 1, the mass ratio of nickel and cobalt metals is 3:1 to 10:1; the molar ratio of the added amount of ethylene glycol to the total molar ratio of nickel and cobalt is 1:0.5 to 1:1.5; and the mass of water in the mixed solution is 92.1% to 94.1%, more preferably 93.1%.
[0014] Preferably, in the step three, the size of the nickel-cobalt nanoparticles formed is 5 to 6 nm; in the catalyst obtained in step three, the loading amount of nickel and cobalt is 5.5 wt% to 12 wt% of the total mass of the catalyst, wherein the nickel loading amount is 5 wt% to 10 wt% and the cobalt loading amount is 0.5 wt% to 3 wt%.
[0015] The catalyst prepared by the above preparation method is used for the methane dry reforming reaction of methane and carbon dioxide to produce synthesis gas H2 / CO.
[0016] Compared with the prior art, the catalyst prepared by the present invention has the following advantages:
[0017] 1) The present invention adopts a simple one-pot impregnation method, in which the nickel-cobalt metal precursor, surfactant and carrier are mixed and then heated and evaporated. Compared with the traditional impregnation method, the preparation method is simpler, and the obtained catalyst metal particles can all enter the carrier pores, so that the catalyst has the advantages of small metal particle size, high dispersion and high stability.
[0018] 2) The present invention uses non-precious metals as catalyst active materials, which are low in price and suitable for industrial large-scale preparation compared to traditional precious metal catalysts.
[0019] 3) The method of the present invention adds a small amount of Co to nickel metal to enhance the light absorption capacity compared to single metal nickel; a certain amount of cobalt is added to the nickel-based catalyst as a photocatalytic active site, and the formed bimetallic catalyst has better photocatalytic activity than the single metal nickel catalyst, which significantly improves the catalytic performance in photothermal synergistic catalysis.
[0020] 4) The present invention uses ethylene glycol as a surfactant. The addition of ethylene glycol causes the metal particles to be selectively anchored in the mesoporous channels during the drying process. The present invention confines the nickel-based catalyst that is prone to carbon deposition and sintering in the mesoporous channels. The smaller scale and larger dispersion give the catalyst a relatively good ability to resist carbon deposition and sintering, thereby improving the catalyst stability. Confining the metal catalyst in the mesoporous channels of SBA-15 can bring about a significant "confined heat" effect to the catalyst, improve the thermal utilization rate, and improve the performance of the confined catalyst under the same conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 TEM images of some embodiments and comparative examples;
[0022] Among them, (a) is the TEM image of comparative example 1, (b) is the TEM image of comparative example 2, and (c) is the TEM image of comparative example 2; (d) and (e) are TEM images of different scales of Example 1; (f) is the HR-TEM image of Example 1;
[0023] (g), (h), and (i) are HAADF and element distribution images of Example 1. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is described in detail below through embodiments, but the protection scope of the present invention is not limited to the embodiments.
[0025] All raw materials in the embodiments of the present invention can be purchased from the market, and the mesoporous molecular sieve SBA-15 is purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0026] Example 1
[0027] Weigh 222.93 mg nickel nitrate hexahydrate, 24.7 mg cobalt nitrate hexahydrate and 500 mg SBA-15, add them to 47.43 μl ethylene glycol and 4053 μl water. Stir and evaporate to dryness in an oil bath heated at 60 ° C, and then put into an oven at 105 ° C to dry overnight. The dried sample was first ground for 10 minutes and then placed in a tube furnace. The heating rate was 2 ° C / min in an air atmosphere, and it was calcined at 450 ° C for 2 hours and then cooled to room temperature. The air flow rate was 80 mL / min. Hydrogen was used for programmed temperature reduction. Ar was first passed to remove the air in the tube furnace and then switched to H2. The flow rate was 20 mL / min, the heating rate was 10 ° C / min, and it was reduced at 700 ° C for 2 hours. The formed nickel-cobalt bimetallic nanoparticles were evenly anchored in the mesoporous carrier, and a nickel-cobalt bimetallic methane dry reforming catalyst grown in ordered mesopores was obtained.
[0028] Example 2
[0029] Weigh 198.16 mg nickel nitrate hexahydrate, 49.41 mg cobalt nitrate hexahydrate and 500 mg SBA-15, add them to 47.43 μl ethylene glycol and 4052 μl water. Stir and evaporate to dryness in an oil bath heated at 60 ° C, and then put into an oven at 105 ° C to dry overnight. The dried sample was first ground for 10 minutes and then placed in a tube furnace. The heating rate was 2 ° C / min in an air atmosphere, and it was calcined at 450 ° C for 2 hours and then cooled to room temperature. The air flow rate was 80 mL / min. Hydrogen was used for programmed temperature reduction. Ar was first passed to remove the air in the tube furnace and then switched to H2. The flow rate was 20 mL / min, the heating rate was 10 ° C / min, and it was reduced at 700 ° C for 2 hours to form nickel-cobalt bimetallic nanoparticles uniformly anchored in the mesoporous carrier, and a nickel-cobalt bimetallic methane dry reforming catalyst grown in ordered mesopores was obtained.
[0030] Example 3
[0031] Weigh 77.86 mg of nickel oxalate dihydrate, 7.76 mg of cobalt oxalate dihydrate and 500 mg of SBA-15, and add them to 47.43 μl of ethylene glycol and 4053 μl of water. Stir and evaporate to dryness in an oil bath at 40 °C and put into an oven at 90 °C to dry overnight. The dried sample was first ground for 10 min and then placed in a tube furnace. The heating rate was 2 °C / min in an air atmosphere. After calcination at 400 °C for 2 h, it was cooled to room temperature with an air flow rate of 50 mL / min. Hydrogen was used for programmed temperature reduction. Ar was first passed to remove the air in the tube furnace and then switched to H2. The flow rate was 10 mL / min, the heating rate was 10 °C / min, and the reduction was carried out at 500 °C for 2 h. The formed nickel-cobalt bimetallic nanoparticles were evenly anchored in the mesoporous carrier, and a nickel-cobalt bimetallic methane dry reforming catalyst grown in ordered mesopores was obtained.
[0032] Example 4
[0033] Weigh 190.84 mg of nickel acetate tetrahydrate, 63.47 mg of cobalt acetate tetrahydrate and 500 mg of SBA-15, and add them to 47.43 μl of ethylene glycol and 4053 μl of water. Stir and evaporate to dryness in an oil bath at 40 °C and then put into an oven at 120 °C to dry overnight. The dried sample was first ground for 10 min and then put into a tube furnace. The heating rate was 2 °C / min in an air atmosphere, and it was calcined at 600 °C for 2 h and then cooled to room temperature. The air flow rate was 100 mL / min. Hydrogen was used for programmed temperature reduction. Ar was first passed to remove the air in the tube furnace and then switched to H2. The flow rate was 40 mL / min, the heating rate was 10 °C / min, and it was reduced at 700 °C for 2 h. The formed nickel-cobalt bimetallic nanoparticles were evenly anchored in the mesoporous carrier, and a nickel-cobalt bimetallic methane dry reforming catalyst grown in ordered mesopores was obtained.
[0034] Comparative Example 1
[0035] Weigh 222.93 mg of nickel nitrate hexahydrate, 24.7 mg of cobalt nitrate hexahydrate and 500 mg of SBA-15 and add them to 10 ml of water. Stir and evaporate to dryness in an oil bath heated at 60 ° C and put into an oven at 105 ° C to dry overnight. The dried sample was first ground for 10 minutes and then placed in a tube furnace. The heating rate was 2 ° C / min in an air atmosphere. After calcination at 450 ° C for 2 hours, it was cooled to room temperature with an air flow rate of 80 mL / min. Hydrogen was used for programmed temperature reduction. Ar was first passed to remove the air in the tube furnace and then switched to H2. The flow rate was 20 mL / min, the heating rate was 10 ° C / min, and it was reduced at 700 ° C for 2 hours. The formed nickel-cobalt bimetallic nanoparticles were evenly distributed between the carriers to obtain a nickel-cobalt bimetallic methane dry reforming catalyst.
[0036] Comparative Example 2
[0037] Weigh 247.78 mg of nickel nitrate hexahydrate and 500 mg of SBA-15, add them to 47.43 μl of ethylene glycol and 4053 μl of water. Stir and evaporate to dryness in an oil bath heated at 60 ° C, and then put it into an oven at 105 ° C to dry overnight. The dried sample was first ground for 10 minutes and then placed in a tube furnace. The heating rate was 2 ° C / min in an air atmosphere, and it was calcined at 450 ° C for 2 hours and then cooled to room temperature. The air flow rate was 80 mL / min. Hydrogen was used for programmed temperature reduction. Ar was first passed to remove the air in the tube furnace and then switched to H2. The flow rate was 20 mL / min, the heating rate was 10 ° C / min, and it was reduced at 700 ° C for 2 hours to form nickel metal nanoparticles uniformly anchored in the mesoporous carrier, and a nickel single metal methane dry reforming catalyst grown in ordered mesopores was obtained.
[0038] Comparative Example 3
[0039] Weigh 247.78 mg of nickel nitrate hexahydrate and 500 mg of SBA-15, add them to 23.72 μl of ethylene glycol and 4053 μl of water. Stir and evaporate to dryness in an oil bath heated at 60 ° C, and then put it into an oven at 105 ° C to dry overnight. The dried sample was first ground for 10 minutes and then placed in a tube furnace. The heating rate was 2 ° C / min in an air atmosphere, and it was calcined at 450 ° C for 2 hours and then cooled to room temperature. The air flow rate was 80 mL / min. Hydrogen was used for programmed temperature reduction. Ar was first passed to remove the air in the tube furnace and then switched to H2. The flow rate was 20 mL / min, the heating rate was 10 ° C / min, and it was reduced at 700 ° C for 2 hours to form nickel metal nanoparticles uniformly anchored in the mesoporous carrier, and a nickel single metal methane dry reforming catalyst grown in ordered mesopores was obtained.
[0040] Comparative Example 4
[0041] Weigh 247.78 mg of nickel nitrate hexahydrate and 500 mg of SBA-15, add them to 71.15 μl of ethylene glycol and 4053 μl of water. Stir and evaporate to dryness in an oil bath heated at 60 ° C, and then put it into an oven at 105 ° C to dry overnight. The dried sample was first ground for 10 minutes and then placed in a tube furnace. The heating rate was 2 ° C / min in an air atmosphere, and it was calcined at 450 ° C for 2 hours and then cooled to room temperature. The air flow rate was 80 mL / min. Hydrogen was used for programmed temperature reduction. Ar was first passed to remove the air in the tube furnace and then switched to H2. The flow rate was 20 mL / min, the heating rate was 10 ° C / min, and it was reduced at 700 ° C for 2 hours. The formed nickel metal nanoparticles were evenly anchored in the mesoporous carrier, and a nickel single metal methane dry reforming catalyst grown in ordered mesopores was obtained.
[0042] In order to study the microscopic appearance and element distribution of several catalysts, TEM, HRTEM and Element mapping were used to test Example 1 and Comparative Examples 1 to 4. The results are as follows: Figure 1 shown.
[0043] Comparative Observation Figure 1 a, b, c, d and e, it can be found that Comparative Example 1 ( Figure 1 There is a significant difference in a), where the metal particle size is much larger than that of comparative example 2 ( Figure 1 b and c) and Example 1 ( Figure 1 In (d and e), the average particle size is 34.8 nm, and the dispersion is also very low. It can be clearly observed that the metal is outside the SBA-15 pores, and almost no metal components can be observed in the pores. Figure 1 In b, c, d and e, similar high dispersion and small average particle size are shown, and no metal aggregation is observed outside the pores. This is because the surface of SBA-15 lacks hydroxyl groups and exhibits low hydrophilicity, making it difficult for nickel nitrate aqueous solution to enter the pores, so the nickel-cobalt nanoparticles are all aggregated outside the pores of SBA-15.
[0044] On the contrary, ethylene glycol was added during the preparation of Comparative Example 2 and Example 1. Ethylene glycol can significantly reduce the surface tension of the nickel nitrate aqueous solution, and the surface tension will further decrease as the concentration of ethylene glycol increases during the evaporation of water. Low surface tension is more conducive to wetting SBA-15, and can accelerate diffusion so that the solution is injected into the deeper pores of SBA-15. In addition, the viscosity of the solution will gradually increase with the evaporation of water, which can enhance the interaction between the solution that has diffused into the pores and SBA-15, effectively preventing the solution from redispersing. Therefore, Comparative Example 2 ( Figure 1 b and c) and Example 1 ( Figure 1d and e) show small particle size, high dispersion and the nanoparticles are confined in the SBA-15 pores, wherein the average particle size of Example 1 is 5.01 nm.
[0045] From the high-resolution transmission electron microscopy (HRTEM) image of Example 1 ( Figure 1 In f), a lattice spacing of 0.212 nm can be found on a nanoparticle, which is different from 0.203 nm of Ni (111) and 0.205 nm of Co (111), indicating that NiCo forms a bimetallic alloy. High-angle annular dark field (HAADF) and energy spectrum (Element mapping) show that Ni and Co appear in the same position, further confirming that the nanoparticles in Example 1 are not single metal Ni or single metal Co.
[0046] Depend on Figure 1 As can be seen from the d-i diagram, the metal particles are evenly dispersed in the pores of the carrier with good dispersion, without obvious agglomeration and sintering. In addition, the performance comparison between Example 1 and Comparative Example 1 also indirectly reflects that the metal in the catalyst of the present invention tends to be evenly distributed, without a large number of agglomerations and exposed sites that lead to deactivation.
[0047] The catalytic performance of the catalysts prepared in the above examples and comparative examples was tested, and the results were as follows:
[0048] 1) The photothermal catalytic performance at 700°C of Examples 1 to 4 is shown in Table 1.
[0049] Table 1. Comparison of photothermal catalytic performance at 700°C in Examples 1-4
[0050]
[0051] Under the condition of constant light intensity, the catalytic performance increases with the increase of the temperature of the external heat source, because the DRM reaction is a strong endothermic reaction, and high temperature can promote the reaction in the positive direction. The effect of Example 1 is the best in photothermal catalysis, which shows that Ni and Co produce a synergistic effect in photothermal catalysis and promote the DRM reaction.
[0052] The hydrogen yield of the photothermal synergistic catalysis (700°C) of Example 1 reached 1151 mmol / g / h, which is 1.9 times the sum of photocatalysis and thermal catalysis (700°C). It can be seen that the effect of photothermal synergistic catalysis is not a simple addition of photocatalysis and thermal catalysis, but a result of combining the advantages of both by complementing each other on the basis of the two.
[0053] The photothermal catalytic methane dry reforming performance of Example 2 is not as good as that of Example 1. This is because the reaction activity of cobalt metal is not as good as nickel under high-temperature photothermal catalysis. Therefore, increasing the proportion of cobalt metal will lead to a decrease in catalytic activity.
[0054] The photothermal catalytic methane dry reforming performance of Example 3 is significantly different from that of the first two examples. The conversion rates of methane and carbon dioxide are both reduced to less than 40%, and the yields of hydrogen and carbon monoxide are less than 500 mmol / g / h. The reason is that reducing the total metal loading will lead to a significant reduction in catalytic performance.
[0055] Example 4 shows that increasing the total metal loading compared to Example 1 and Example 2 does not significantly improve the catalytic performance. In the long-term test, the deactivation of this example is more obvious than that of Example 1. It is considered that the excessively high metal loading leads to metal agglomeration and increased carbon deposition, resulting in poor stability.
[0056] 2) The results of the photothermal 700°C catalytic performance comparison between Comparative Examples 1 to 4 and Example 1 are shown in Table 2:
[0057] Table 2 Comparison of photothermal catalytic performance at 700°C between comparative examples 1, 3, 4 and example 1
[0058]
[0059] The catalyst prepared in Comparative Example 1 was significantly deactivated in the photothermal catalytic methane dry reforming reaction. This is because compared with Example 1, the ethylene glycol co-impregnation method was not used in the catalyst preparation of this comparative example. Without the addition of ethylene glycol, the metal particles tended to be evenly distributed among the carriers during the drying process, rather than selectively anchored in the mesoporous channels. A large number of metal particles were exposed on the surface and agglomerated, which easily led to deactivation. Figure 1 From a to c, it can be observed that a large number of metal particles are exposed on the surface and aggregated, which can easily lead to deactivation.
[0060] Compared with Example 1, the photothermal catalytic methane dry reforming performance of Comparative Example 2 is very similar, but the stability performance is not as good as Example 1, especially in the photocatalytic test, which confirms that the addition of a small amount of cobalt can promote the photothermal catalytic stability of the catalyst.
[0061] The performance of Comparative Example 3 is between Example 1 and Comparative Example 1, and the stability is not good, but the deactivation speed is not as fast as Comparative Example 1, indicating that reducing the amount of ethylene glycol can easily reduce the dispersion of metal particles and increase the average particle size. This reflects that reducing the amount of ethylene glycol cannot make all metal particles evenly dispersed in the mesoporous channels.
[0062] The catalytic performance of Comparative Example 4 is not significantly different from that of Example 1, indicating that increasing the amount of ethylene glycol does not bring about a significant improvement in metal dispersion, and its catalyst configuration is consistent with that in Example 1.
[0063] In the catalyst prepared by the present invention, bimetallic nickel-cobalt nanoparticles are uniformly dispersed in the open mesoporous channels of the SBA-15 carrier, and the channel wall can play a confining role, so the growth of nickel-cobalt nanoparticles can be well suppressed, thereby greatly reducing the degree of carbon deposition. At the same time, the silicon dioxide wall also provides a certain heat insulation effect, forming local high temperature near the nickel-cobalt quantum dots in the photothermal synergistic catalysis, that is, "local hot spots", thereby promoting the methane dry reforming reaction. Therefore, the catalyst is a nanocatalyst with good catalytic performance and simple preparation process in methane reforming.
[0064] The catalyst of the present invention has bimetallic loading in open mesoporous channels, which can effectively form local hot spots in photothermal catalysis and has a certain macroscopic mass transfer capacity for methane dry reforming (DRM) of gas-gas reaction, thereby achieving better photothermal synergistic effect.
[0065] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention.
Claims
1. A method for preparing a mesoporous confined nickel-based methane dry reforming catalyst, characterized in that: The catalyst uses a mesoporous molecular sieve as a carrier, and nickel and cobalt are confined in the pores of the mesoporous molecular sieve; the nickel and cobalt are evenly distributed in the pores.
2. The preparation method according to claim 1, characterized in that: The pore size of the mesoporous molecular sieve is 6nm-11nm, the material of the mesoporous molecular sieve is silicon dioxide, and the mesoporous molecular sieve is SBA-15; the loading amount of nickel and cobalt is 5.5wt%-12wt% of the total mass of the catalyst, wherein the nickel loading amount is 5wt%-10wt%, and the cobalt loading amount is 0.5wt%-3wt%.
3. The preparation method according to claim 1, characterized in that: The method comprises the following steps: Step 1: Mix a nickel precursor salt, a cobalt precursor salt, an SBA-15 carrier and an appropriate amount of ethylene glycol in a certain amount of water to obtain a mixed solution, stir and evaporate the mixed solution under the condition of heating in an oil bath at 40° C. to 80° C., and then dry at 90° C. to 120° C. for at least 12 hours; Step 2: Grind the dried sample for 10-15 minutes and then put it into a tube furnace. Calcinate it in an air atmosphere for 2-6 hours and then cool it to room temperature. The calcination conditions are: 400-600°C, a heating rate of 2°C / min, and an air flow rate of 50-100 mL / min. Step 3: Use hydrogen programmed temperature reduction, first pass Ar to remove the air in the tubular furnace and then switch to H2, with an H2 flow rate of 10-40 mL / min, a heating rate of 10°C / min, and reduction at 500°C-700°C for 2h-6h. The formed nickel-cobalt bimetallic nanoparticles are evenly anchored in the mesoporous carrier, and a nickel-cobalt bimetallic methane dry reforming catalyst grown in ordered mesopores is obtained.
4. The preparation method according to claim 3, characterized in that: In the step 1, the nickel precursor salt is nickel nitrate hexahydrate, nickel acetate tetrahydrate or nickel oxalate dihydrate, and the cobalt precursor salt is cobalt nitrate hexahydrate, cobalt acetate tetrahydrate or cobalt oxalate dihydrate.
5. The preparation method according to claim 3, characterized in that: In the step 1, the mass ratio of the nickel and cobalt metals is 3:1 to 10:1; the molar ratio of the added amount of ethylene glycol to the total amount of nickel and cobalt is 1:0.5 to 1:1.5; and the mass of water in the mixed solution is 92.1% to 94.1%.
6. The preparation method according to claim 3, characterized in that: In the step 3, the size of the nickel-cobalt nanoparticles formed is 5 to 6 nm; in the catalyst obtained in step 3, the loading amount of nickel and cobalt is 5.5 wt% to 12 wt% of the total mass of the catalyst, wherein the nickel loading amount is 5 wt% to 10 wt% and the cobalt loading amount is 0.5 wt% to 3 wt%.
7. The catalyst prepared by the preparation method according to any one of claims 1 to 6 is used for methane dry reforming reaction of methane and carbon dioxide to produce synthesis gas H2 / CO.
Citation Information
Cited By
Catalyst as well as preparation method and application thereof
CN121847143A
A catalyst, its preparation method and application
CN121847143B